Pengukuran dan Evaluasi Kinerja Manajemen PNS Di Daerah - SamiajiÂ SamiajiÂ (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
PNS described having a low level of professionalism, service capability that is not optimal, low levels of reliability, assurance, tangibility, empathy and responsiveness, do not have this level of integrity as government officials so as not to have an emotional tie to the agency force and duties, authority abuse height (KKN), a low level of well-being and is not associated with education level, performance, productivity and discipline. These conditions have an impact on the performance of low PNS in discharging its duties and obligations in serving the community. One of the causes of poor performance in delivering public services PNS is weak PNS management itself, which began in the planning up to the cessation of PNS findings indicate the need for changes in management aspects of civil servants in the district should be formulated in a clear and decisive in the formulation of the law regulating the civil servants in the district and institutional framework that functionally perform management activities / management of state officials.